Diversité De La Macrofaune Du Sol Dans Les Parcelles De Reboisement De La Grande Muraille Verte Au Sénégal - Tamsire, Samb; Ababacar, Cissé; Baïla, Ndiaye Abdoulaye (European Scientific Journal, ESJ, 2017)
Objective: To assess the effect of vegetation cover on soil macrofauna, a study focused on the diversity of soil macrofauna inside and outside reforestation plots of the Great Green Wall in Senegal was carried out. Methodology: The sampling of macrofauna was performed according to the method recommended by the TSBF network (Tropical Soil Biology and Fertility). It involves isolating 10 ground plots along a transect of 50 meters chosen at random in each plot and outside of each plot. The macrofauna was sampled between February and July 2016 during the dry season Results: The results show, in order of importance Hymenoptera, Isoptera, Coleoptera, the Spiders, the isopods and springtails are the taxonomic groups of the study area. The density of each of these taxa is larger inside and outside of the plots. The vertical distribution of macrofauna shows that the 0-10 cm layer is more densely populated than the deeper layers. Conclusion: This study showed a low diversity of soil macrofauna in the area. It also shows that the vegetation cover affects the density of the macrofauna.